2021
DOI: 10.1016/j.isci.2021.103449
|View full text |Cite
|
Sign up to set email alerts
|

Liver sphingomyelin synthase 1 deficiency causes steatosis, steatohepatitis, fibrosis, and tumorigenesis: An effect of glucosylceramide accumulation

Abstract: Summary Glucosylceramide (GluCer) was accumulated in sphingomyelin synthase 1 (SMS1) but not SMS2 deficient mouse tissues. In current study, we studied GluCer accumulation-mediated metabolic consequences. Livers from liver-specific Sms1 /global Sms2 double-knockout (dKO) exhibited severe steatosis under a high-fat diet. Moreover, chow diet-fed ≥6-month-old dKO mice had liver impairment, inflammation, and fibrosis, compared with wild type and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 66 publications
5
14
0
Order By: Relevance
“…We first accessed liver sphingolipid levels and found all tested SM in liver homogenates were dramatically reduced compared to wild type and Sms2 KO as expected ( Figure 4A ). Consistent with the finding in liver-specific Sms1 /global Sms2 dKO mice 24 , we observed that glucosylceramides were accumulated in the liver ( Figure 4B ), which could be directly linked with liver abnormality reflected by increasing plasma alanine aminotransferase (ALT) levels ( Figure 4C ). Surprisingly, ceramide, as a substrate of SMS activity, was reduced in the liver ( Figure 4D ), which is opposite to the plasma ceramide levels ( Figure 2B ).…”
Section: Resultssupporting
confidence: 89%
“…We first accessed liver sphingolipid levels and found all tested SM in liver homogenates were dramatically reduced compared to wild type and Sms2 KO as expected ( Figure 4A ). Consistent with the finding in liver-specific Sms1 /global Sms2 dKO mice 24 , we observed that glucosylceramides were accumulated in the liver ( Figure 4B ), which could be directly linked with liver abnormality reflected by increasing plasma alanine aminotransferase (ALT) levels ( Figure 4C ). Surprisingly, ceramide, as a substrate of SMS activity, was reduced in the liver ( Figure 4D ), which is opposite to the plasma ceramide levels ( Figure 2B ).…”
Section: Resultssupporting
confidence: 89%
“…The fact that liver disease is common in Gaucher disease (41), implicates the critical pathogenic impact of GluCer on hepatic cellular function. In support of this, a recent study indicated that GluCer accumulation in sphingomyelin synthase 1-deficient mouse liver resulted in steatosis, steatohepatitis and fibrosis (42). Consistently, pharmaceutic inhibition of glucosylceramide synthase alleviated the hepatic steatosis and fibrosis in obese mice (43).…”
Section: Discussionmentioning
confidence: 85%
“…S 5 e). Of note, the glucosylceramide species, which affects the function of cells, and may in term lead to liver diseases 34 , were reduced and induced by MO in females and males respectively, leading to higher abundance in males. F-moC had more of the ceramides containing 1-double bond and less of those containing 2-double bonds than M-moC (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In conclusion, phospholipids classes and species are highly sex-dependent. Overall, females have more cardiolipin which is essential for mitochondria function, and less pro-inflammatory mediators such as lysophospholipids, phosphatidylinositol, glucosylceramides, and sphingolipids than males which is correlated with balanced metabolic profile 34 , 35 . Moreover, cardiolipin is the signature lipid of mitochondria, which would indicate more mitochondria mass in females’ livers and hence different capacity for oxidative phosphorylation 36 which will benefit the metabolic profile.…”
Section: Resultsmentioning
confidence: 99%